Determinants of Land and Building Taxpayer Compliance in a Decentralized Tax System: Evidence from Denpasar City - Gede Crisna Wijaya; Ni Putu Khintan Corneliatisa; Dewa Jati Primajana; Diah Pradnyadewi T (Jurnal Ilmiah Akuntansi & Bisnis, 2025)
Taxpayers have the right to have their specific needs met when they participate in national development activities. Accordingly, this research aims to examine the factors influencing the compliance of Land and Building Taxpayers in Denpasar, with a particular focus on the roles of SPPT, Taxpayer Awareness, Service Quality, and Tax Sanctions, within the institutional context of the Denpasar City Regional Revenue Agency. The study covers the entire population of 192,297 active individual taxpayers in the region. To obtain respondents, purposive sampling was applied based on specific criteria, including (1) registered as an active individual taxpayer in Denpasar City, (2) having a history of paying land and building taxes, and (3) being willing to provide complete and accurate information. Using the Slovin formula with a 10% margin of error, a sample size of 100 respondents was determined, ensuring a representative and manageable cohort for detailed analysis. Multiple linear regression analysis was employed to examine the interrelationships among the variables. The results indicate that SPPT, Taxpayer Awareness, Service Quality, and Tax Sanctions all positively influence the compliance of Land and Building Taxpayers in Denpasar City. These findings emphasize the importance of these factors in enhancing taxpayer compliance.